Estimating the Impact of Banking Financial Depth Indicators on the Business Sector in Libya (Economic studies journal, 2025)
This study aimed to demonstrate the relationship between financial depth and business sector indicators in the Libyan economy, especially after the financial developments that occurred in the Libyan banking sector, where annual data were analyzed during the period (1980-2022) using the Autoregressive Distributed Lag (NARDL) model. Results showed that the money supply indicator has a statistically significant impact, both positive and negative effects, on the business sector. Any increase in the money supply will result in an improvement in the business sector, while a decrease will also lead to an improvement in the business sector. This indicates that there is a non-linear relationship between the money supply and the growth of the business sector. At the same time, the results revealed a positive impact of the credit indicator on the growth of the business sector. An increase in the volume of credit will lead to growth in the business sector, while a decrease in the volume of credit had a statistically weak effect. The study also recommended working to create a suitable climate for the business sector by drawing up a policy for commercial banks in terms of (money supply - granting credit loans - determining the size of deposits) in a manner consistent with the conditions for improving the business sector, in addition to lifting banking and administrative restrictions.
Keywords: Financial Depth; Business Sector; Libyan Economy; NARDL Model